Sphingosine 1-phosphate signalling in cancer. (19th January 2012) - Pyne, Nigel J.; Tonelli, Francesca; Lim, Keng Gat; Long, Jaclyn S.; Edwards, Joanne; Pyne, Susan
Abstract : There is an increasing body of evidence demonstrating a critical role for the bioactive lipid S1P (sphingosine 1-phosphate) in cancer. S1P is synthesized and metabolized by a number of enzymes, including sphingosine kinase, S1P lyase and S1P phosphatases. S1P binds to cell-surface G-protein-coupled receptors (S1P1 –S1P5 ) to elicit cell responses and can also regulate, by direct binding, a number of intracellular targets such as HDAC (histone deacetylase) 1/2 to induce epigenetic regulation. S1P is involved in cancer progression including cell transformation/oncogenesis, cell survival/apoptosis, cell migration/metastasis and tumour microenvironment neovascularization. In the present paper, we describe our research findings regarding the correlation of sphingosine kinase 1 and S1P receptor expression in tumours with clinical outcome and we define some of the molecular mechanisms underlying the involvement of sphingosine kinase 1 and S1P receptors in the formation of a cancer cell migratory phenotype. The role of sphingosine kinase 1 in the acquisition of chemotherapeutic resistance and the interaction of S1P receptors with oncogenes such as HER2 is also reviewed. We also discuss novel aspects of the use of small-molecule inhibitors of sphingosine kinase 1 in terms of allosterism, ubiquitin–proteasomal degradation of sphingosine kinase 1 and anticancer activity. Finally, we describe how S1P receptor-modulating agents abrogate S1P receptor–receptor tyrosine kinase interactions, with potential to inhibit growth-factor-dependent cancer progression.